Latin America in colonial times - Restall, Matthew 1964-; Lane, Kris E. 1967- (Cambridge University Press, 2018)
Few milestones in human history are as momentous as the meeting of three great civilizations on American soil in the sixteenth century. The fully revised textbook Latin America in Colonial Times presents that story in an engaging but informative new package, revealing how a new civilization and region - Latin America - emerged from that encounter. The authors give equal attention to the Spanish and Portuguese conquerors and settlers, to the African slaves they brought across the Atlantic, and to the indigenous peoples whose lands were invaded. From the dawn of empires in the fifteenth century, through the conquest age of the sixteenth and to the end of empire in the nineteenth, the book combines broad brushstrokes with anecdotal details that bring the era to life. This new edition incorporates the newest scholarship on Spain, Portugal, and Atlantic Africa, in addition to Latin America itself, with indigenous and African views and women's experiences and contributions to colonial society highlighted throughout.